2022
DOI: 10.1002/ieam.4588
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of pharmaceuticals in the European Vecht River

Abstract: Active pharmaceutical ingredients (APIs) can reach surface waters used for drinking water extraction and recreational activities, such as swimming and fishing. The aim of the present study was to systematically assess the lifetime human health risks posed by 15 individual APIs and their mixtures occurring in the German-Dutch transboundary Vecht River. An exposure model was developed and used to assess the combined risks of oral and dermal exposure under a variety of exposure conditions. A total of 4500 API upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…A previous study detected extremely high concentrations of amoxicillin (87-272.150 ng/L) in drinking water systems, which is linked to the development of ARB, posing a challenge in disease management [45]. In a study, the exposure risks and hazard quotients (HQ) of antibiotics commonly found in drinking water ranged from 10-9 to 2.5 [166]. Doxycycline had the highest HQ, exceeding the risk threshold (HQ=1).…”
Section: Risk Factors and Behavioursmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study detected extremely high concentrations of amoxicillin (87-272.150 ng/L) in drinking water systems, which is linked to the development of ARB, posing a challenge in disease management [45]. In a study, the exposure risks and hazard quotients (HQ) of antibiotics commonly found in drinking water ranged from 10-9 to 2.5 [166]. Doxycycline had the highest HQ, exceeding the risk threshold (HQ=1).…”
Section: Risk Factors and Behavioursmentioning
confidence: 97%
“…All the other antibiotics studied had HQs below the risk threshold, indicating a low likelihood of causing health risks. Risks of pharmaceutical mixtures were higher (HQ ranging from 10 −2 to 2.6) than any individual [166]. Despite the increase in HQ values, the hazard index (HI) fell below those that can cause lifetime health risks.…”
Section: Risk Factors and Behavioursmentioning
confidence: 97%